2011
DOI: 10.3390/molecules16108428
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Synthesis of Isotopically Labeled 5,5-Dimethyl-pyrroline N-Oxide

Abstract: 5,5-Dimethylpyrroline N-oxide (15N) and 5,5-di(trideuteromethyl)pyrroline N-oxide were synthesized from the respective isotopically labeled 2-nitropropane analogs obtained from the reaction of sodium nitrate with 2-halopropanes. This facile, straightforward process allows synthesizing isotopically labeled DMPO analogs in a 4-step reaction without special equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since the initial synthesis of unlabeled DMPO (34,35) several other researchers have synthesized DMPO and its analogs using various routes (36)(37)(38)(39)(40)(41)(42). Based on works of Beth et al (43) and Janzen et al (38), synthesis of labeled DMPO as a spin trap agent was first explored by Pou et al (37).…”
Section: Synthesis Of 13 C-labeled Dmpo (Deepak)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial synthesis of unlabeled DMPO (34,35) several other researchers have synthesized DMPO and its analogs using various routes (36)(37)(38)(39)(40)(41)(42). Based on works of Beth et al (43) and Janzen et al (38), synthesis of labeled DMPO as a spin trap agent was first explored by Pou et al (37).…”
Section: Synthesis Of 13 C-labeled Dmpo (Deepak)mentioning
confidence: 99%
“…Based on works of Beth et al (43) and Janzen et al (38), synthesis of labeled DMPO as a spin trap agent was first explored by Pou et al (37). In order to prepare DMPO with 13 C at position C5 and deuterated protons on neighboring carbons (to prolong the T1 relaxation times) we followed the procedure of Le et al (41) and Leinisch et al (42). We found that the 13 C-C2 deuterated three carbon starting material could be effectively prepared from, the h-d exchange on acetone 13 C-C2 as described in the literature (44) under basic conditions.…”
Section: Synthesis Of 13 C-labeled Dmpo (Deepak)mentioning
confidence: 99%